Strength, mobility, and functional outcomes 2.5 months after hip arthroscopy for femoroacetabular impingement syndrome: A Cross-sectional Study. - Burnel, Joévin; Chamu, Thomas; Bonin, Nicolas; Van Cant, Joachim; Pairot De Fontenay, Benoit (Physical Therapy in Sport, 2025)
Short-term deficits after hip arthroscopy for femoroacetabular impingement syndrome (FAIS) remain poorly understood. We assessed muscle strength, hip range of motion, and functional task performance 2.5 months after surgery and analyzed their association with self-reported function. Cross sectional study. 52 patients. Maximal isometric strength (hip flexion with both straight and flexed hip/knee, abduction and external rotation), hip range of motion (flexion, external and internal rotation), and functional tasks (bipodal/unipodal squat, bilateral vertical jump, single-leg distance hop). Between-limb differences were analyzed using paired t-tests, and the Limb Symmetry Index (LSI) was calculated. The operated hip showed lower hip flexion strength (LSI = 88.4%; ES = −0.549; p < 0.001) and reduced range of motion (LSI = 75.4–92.4%; ES = −0.479 to −1.02; all p < 0.01) compared to the non-operated hip. Functional task performance did not differ between operated and non-operated hips (all p > 0.05). Patients showed alterations in hip flexion strength and range of motion post-surgery, but functional task performance was unaffected. Targeted assessment and intervention may be needed to improve outcomes after surgery for FAIS. • Hip rotation at 90° flexion is significantly reduced at 2.5 months after surgery. • Hip flexor strength with the hip/knee straight is decreased at 2.5 months post-op. • No differences in functional task performance were observed at 2.5 months post-operatively. • Prioritize assessment of range of motion and strength early in rehabilitation.